Clinical and economic justification of screening for mucopolysaccharidosis type I in children at groups of risks - I. S. Krysanov; V. S. Krysanova; V. Yu. Ermakova (Izdatelstvo OKI, 2021)
Background. Mucopolysaccharidosis Type I (MPS I) has clinical heterogeneity without specific symptoms leading to difficulties with diagnostic on time. In-depth screening for MPS I in children has aim of early detection and timely treatment with an enzyme replacement therapy. Aim. The purpose of this study was to conduct a clinical and economic assessment of the feasibility of screening for MPS I in children at group of risks. Materials and methods. Model for evaluation of the social-economic burden of MPS I with calculation of expenditures has been created. Costs of diagnosed and non-diagnosed patients in group of risks were identified, including direct medical costs (pharmacotherapy, out-patient cure, hospital admission, complications treatment, hematopoietic stem cell transplantation; direct non-medical (payments for disability); indirect (expenses related to the reduction or loss of the ability to work of one of the parents performing the duties of caring for a disabled child). Results. The weighted average cost per 1 diagnosed patient with mild forms of MPS I with selective screening, was 405,974.22 rubles, which is 184,421.85 rubles less vs average cost per 1 undiagnosed patient. The management and treatment of patients with mild forms of MPS I after selective screening will allow saving up to 17.7 million rubles/year, which would possible to additionally screen 705 patients. Taking into account the size of the population of patients with undiagnosed MPS I, currently the costs for this group amount to 56.7 million rubles, while the «overspend» of budget funds for untimely diagnosis of MPS I for this cohort of children is about 22.6 million rubles/year. Conclusion. Selective screening for MPS I in children at group of risks is economically proved and can lead to treatment on-time for disability and complications prevention.